Contraception use and unplanned pregnancies among injection drug-using women in St Petersburg, Russia. - Abdala, Nadia; Kershaw, Trace; Krasnoselskikh, Tatiana V; Kozlov, Andrei P (The journal of family planning and reproductive health care / Faculty of Family Planning & Reproductive Health Care, Royal College of Obstetricians & Gynaecologists, 2011)
This cross-sectional study estimated the prevalence of contraceptive methods and investigated whether abortion rates influence contraceptive behaviour among injection drug-using (IDU) women in St Petersburg, Russia.
Keywords: Abortion, Induced; Adolescent; Adult; Condoms; Contraception Behavior; Contraceptives, Oral, Hormonal; Cross-Sectional Studies; Female; Humans; Pregnancy; Pregnancy, Unplanned; Russia; Sexual Behavior; Substance Abuse, Intravenous